Gyana/Pragya Paradigm for Professional Development of Teachers: A Socio-Cultural Perspective - Dhungana, Parbati; Luitel, Bal Chandra (Journal of Interdisciplinary Studies in Education, 2022)
The existing Western Modern Worldviews (i.e. post/positivism) or western induced paradigm/s (e.g. critical and postmodern) seem insufficient for ensuring harmonious learning spaces in the context of continuous professional development of Nepali school teachers. In this chapter, we discuss context-responsive socio-cultural perspectives of multiple Eastern Wisdom Traditional (EWT) belief systems such as prasna (question), kalaa (art), and artha (meaning) that contribute to harmonious professional learning spaces (inner and outer) for teachers in Nepal. Then we introduce gyana/pragya, an integral paradigm, as a multi-paradigmatic research design space for creating and sustaining harmony in the professional setting and within co-researchers. This research explores the possibility of conducting educational research (e.g. Teachers Professional Development) by adapting multiple EWT belief systems. At last, we share enhanced harmony, an inherent quality of teachers and teacher educators as/for professional development.